Damage caused intentionally and insurance liability: legislative changes and disobedience of the Supreme Court announced (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
Despite the apparent clarity of the terms of the Insurance Contract Law, the issue of coverage of mens rea under liability to the public is far from clear. Moreover, in the specific field of liability to the public in driving insurance, despitethe apparent clarity of the terms of such law, which expressly state (and havedone so for a number of years) that any damages caused intentionally by means ofthe use of a motor vehicle (i.e. the use of an automobile as a lethal weapon rather than as a mode of transport) will not be deemed a driving offence, it appears thatthe Supreme Court of Justice neglects to pay much attention to that which is providedfor by law.
Keywords: mens rea; driving; insurance; negligence